URDU 2 SOCIAL AND CLASS AWARENESS IN SABIR ZAFAR’S GHAZAL: صابر ظفر کی غزل میں طبقاتی اورسماجی شعور - Ayaz, Jindwada; Rafique, Robina (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2021)
Great scholars and writers in every epoch have struggled to determine the actual human position so that humanity should be driven in a right direction. Sabir Zafar belongs to such a decade of 1970’s who’s 45 poetic volumes have been published from 1974 to present. Sabir Zafar put his expertise in songs and Ghazal but his skill lies in Ghazal writing. He reflects penetrative experiences through his Ghazal. Sabir Zafar has analysed the unstable behaviours and characters and made them. The topic of his Ghazal. The classical traits like simplicity, comprehension and fluency are found in his poetry. Social and stratum awareness and its development is repleted in his poetry quite clearly. He rendered his motive through poetry by deploying similies and metaphors. He considered the oppression, injustice, inequality, and lack of tolerance as destabilizing the society. He seems very vigilant and vocal against these oppressive practices through his Ghazal. His Ghazal contain political, social and religious thoughts. The poetry of Sabir Zafar airs against cruelty and social discrimination, whether it is human right violation or massacre or terrorism or kidnapping, Sabir Zafar’s pen seems to travel through all mazes, he seems protesting without fearing from any consequences.